2020
DOI: 10.3168/jds.2019-17826
|View full text |Cite
|
Sign up to set email alerts
|

Productive life span and resilience rank can be predicted from on-farm first-parity sensor time series but not using a common equation across farms

Abstract: A dairy cow's lifetime resilience and her ability to recalve gain importance on dairy farms, as they affect all aspects of the sustainability of the dairy industry. Many modern farms today have milk meters and activity sensors that accurately measure yield and activity at a high frequency for monitoring purposes. We hypothesized that these same sensors can be used for precision phenotyping of complex traits such as lifetime resilience or productive life span. The objective of this study was to investigate whet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 32 publications
3
68
0
1
Order By: Relevance
“…Simple examples follow. The data from each milking is one of the most useful to monitor the risk of mastitis [ 20 ]. This result, jointly with other sensors for early mastitis detection, allows a positive feedback in maintaining high milk yield in the short time as well as in the whole lactation performance (305-d milk yield).…”
Section: Discussionmentioning
confidence: 99%
“…Simple examples follow. The data from each milking is one of the most useful to monitor the risk of mastitis [ 20 ]. This result, jointly with other sensors for early mastitis detection, allows a positive feedback in maintaining high milk yield in the short time as well as in the whole lactation performance (305-d milk yield).…”
Section: Discussionmentioning
confidence: 99%
“…24 hours), while the Lely AMS software, before storage, corrects for the varying number of milkings per day per cow when milking with AMS. To obtain a similar variance as for the Lely milk production data, the daily milk production time series of DeLaval farms were smoothed with a moving average using a span of 3 days before the analysis (Adriaens et al, 2020). The second data set for Lely AMS systems contained all data since the installation of the AMS and thus matches with the daily data, whereas for DeLaval systems the second data set typically comprised a shorter period compared to the daily data.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work showed that mastitis influences the lactation curves, and therefore classical lactation models including the entire time series cannot be used as such (Andersen et al, 2011). Several authors have recently developed methodologies that predict the unperturbed milk yield trajectory of a cow (Adriaens et al, 2020(Adriaens et al, , 2021Poppe et al, 2020;Ben Abdelkrim et al, 2021), from which the residuals can be used to quantify deviations. The methodology that we developed previously has the advantage of being applicable for QMY trajectories too, which allowed us to use an similar method at both the cow and the quarter level in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations